2007
DOI: 10.1002/humu.20450
|View full text |Cite
|
Sign up to set email alerts
|

Truncation ofNHEJ1 in a patient with polymicrogyria

Abstract: Polymicrogyria (PMG) is a common malformation of the human cerebral cortex for which both acquired and genetic causes are known. Although genetic heterogeneity is documented, only one gene is currently known to cause isolated PMG. To clone new genes involved in this type of cerebral malformation, we studied a fetus presenting a defect of cortical organization consisting of a polymicrogyric cortex and neuronal heterotopia within the white matter. Karyotype analysis revealed that the fetus was carrier of a balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 35 publications
0
14
0
3
Order By: Relevance
“…The patient displayed a marked neurological phenotype substantially more severe than that of previously described LIGIV syndrome or XLF-deficient patients, who normally show mild microcephaly (20,21). The cortical disorganization bears some resemblance to the malformation described in a fetus carrying a balanced translocation that disrupted the gene encoding XLF (43). The fetus had posterior predominant polymicrogyria with extension to the frontal lobe, and small groups of heterotopic neurons in the white matter.…”
Section: Discussionmentioning
confidence: 69%
“…The patient displayed a marked neurological phenotype substantially more severe than that of previously described LIGIV syndrome or XLF-deficient patients, who normally show mild microcephaly (20,21). The cortical disorganization bears some resemblance to the malformation described in a fetus carrying a balanced translocation that disrupted the gene encoding XLF (43). The fetus had posterior predominant polymicrogyria with extension to the frontal lobe, and small groups of heterotopic neurons in the white matter.…”
Section: Discussionmentioning
confidence: 69%
“…16 Moreover Cantagrel et al 17 described a patient with hydrocephalus, polymicrogyria and syndactyly of the fingers and toes, who carried a balanced translocation t(2;7)(q36;p22), the breakpoint on chromosome 2 disrupting NHEJ1, a gene also located within the duplicated region in our cases. 17 Seen as the mechanism underlying these phenotypes is rather loss-of-function, we consider NHEJ1 unlikely to be primarily involved in the phenotype seen in this study. We conclude that the duplication's effect on IHH is most likely the main phenotypic determinant in our cases, but we cannot exclude an additive or modifying influence of other genes located in the duplications.…”
Section: Ihh Duplication In Acsmentioning
confidence: 78%
“…This could be attributable to loss of function of any of the genes within the interval for which homozygous mice have not yet been described, and/or to homozygosity for the ectopic Ihh expression defect. Interestingly a recent study reported a human fetus with a balanced de novo translocation t(2;7)(q36;p22) with the chromosome 2 breakpoint interrupting the orthologue of Nhej1 at a position similar to the start of the Dbf deletion (Cantagrel et al, 2007). The consequence of this translocation, as in Dbf , would be to isolate the human IHH gene from possible regulatory sequences present on the opposite side of the NHEJ1 breakpoint.…”
Section: Discussionmentioning
confidence: 99%